Two Non-Necrotic Disease Resistance Types Distinctly Affect the Expression of Key Pathogenic Determinants of Xanthomonas euvesicatoria in Pepper - Zoltán Bozsó; Dániel Krüzselyi; Ágnes Szatmári; Gábor Csilléry; János Szarka; Péter G. Ott (Plants, 2022)
Pepper (Capsicum annuum L.) carrying the gds (corresponding to bs5) gene can prevent the development of bacterial leaf spot disease without HR. However, little is known regarding the development of the resistance mechanism encoded by gds, especially its influence on the bacterium. Here, the effect of gds was compared with pattern-triggered immunity (PTI), another form of asymptomatic resistance, to reveal the interactions and differences between these two defense mechanisms. The level of resistance was examined by its effect on the bacterial growth and in planta expression of the stress and pathogenicity genes of Xanthomonas euvesicatoria. PTI, which was activated with a Pseudomonas syringae hrcC mutant pretreatment, inhibited the growth of Xanthomonas euvesicatoria to a greater extent than gds, and the effect was additive when PTI was activated in gds plants. The stronger influence of PTI was further supported by the expression pattern of the dpsA bacterial stress gene, which reached its highest expression level in PTI-induced plants. PTI inhibited the hrp/hrc expression, but unexpectedly, in gds plant leaves, the hrp/hrc genes were generally expressed at a higher level than in the susceptible one. These results imply that different mechanisms underlie the gds and PTI to perform the symptomless defense reaction.